Supplementary material 2 from: Soreng RJ, Gillespie LJ (2018) Poa secunda J. Presl (Poaceae): a modern summary of infraspecific taxonomy, chromosome numbers, related species and infrageneric placement based on DNA. PhytoKeys 110: 101-121. https://doi.org/10.3897/phytokeys.110.27750 - Soreng, Robert John; Gillespie, Lynn J. (Zenodo, 2018)
David D. Keck's annotations of taxa here included in Poasecunda : Explanation note: The following taxa recognised by Keck, but included by us in P.secunda s.l., are given in the specimen annotation lists: P.ampla, P.canbyi, P.gracillima, P.incurva, P.juncifolia, P.nevadensis, P.sandbergii and P.scabrella. His lists focused on western Continental United States species but included some mainly non-arctic Alaskan, Canadian and Mexican (Baja California) records and some records of eastern United States species. Copies of the original typed lists are stored in the reprint files in the Grass Lab in the Department of Botany, Smithsonian Institution. Optical character recognition (OCR) was performed on the present selection to allow the lists to be searchable to a large degree. Keck's annotations are considered to be sound and to represent hundreds of historical collections widely distributed in herbaria as vouchers for P.secunda infraspecies. We treat P.ampla, P.juncifolia and P.nevadensis as varieties of P.secundasubsp.juncifolia (vars. ampla, juncifolia and nevadensis, respectively) in our revised classification. The remaining taxa are treated as varieties of P.secundasubsp.secunda , as follows: var. gracillima (P.gracillima), var. scabrella (P.scabrella) and var. secunda (P.canbyi, P.incurva, and P.sandbergii).